Influence of feeding protected protein and energy on intake and digestion by lambs - Mathius, I-W; Haryanto, B; Susana, I.W.R (Indonesian Animal Sciences Society, 1998)
To determine the effect of additional protected protein and energy on intake and digestion in lambs, a trial was conducted using 36 young sheep (average body weight 24 .8 _+ 1 .7 kg) in a completely randomized design . Combination of three levels of protected protein (0, 10 and 20%, based on the dry matter of the concentrate offered) and three levels of protected energy (0, 5, 10%, based on the dry matter of the concentrate offered) were added into concentrate diet and fed to growing sheep. Results showed that different levels of feed additive did not affect (P>0 .05) intake of dry matter, organic matter, neutral detergent fiber, acid detergent fiber and metabolizable energy, with average of 76 .3 g, 68.9 g, 31 .2 g, 16 .79 g and 0.75 MJ /kg BW0.75 respectively . Level of protected protein gave significant (P<0 .05) respons on crude protein intake (7 .4 vs 8.7 vs 9.8 g/kg BW0.75) . Combination of protected protein and energy did not affect animal ability to digest the nutrient effectively. A mixtures of 20 % protected protein and 5 %energy addition into concentrate diet increased average daily gain (ADG) as much as 100 g. It was also found that for every gram ADG needs 42.2 kJ metabolizable energy . Â Key words : Protein, protected energy, sheep